THE EFFECT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON THE USE OF E-LEARNING WITH TAM MODEL IN FACULTY OF ECONOMICS STUDENT OF JAKARTA STATE UNIVERSITY - Maharani, Melwanda Rieka; Usman, Osly; Marsofiyati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
The purpose of this study to determine the effect of perceived usefulness and perceived ease of use on the use of e-learning with the TAM model on FE UNJ students. The method used is a survey method. The affordable population in this study amounted to 303 students with a sample of 161 students. The data analysis technique used is the first measurement of the outer model consisting of Cronbach's alpha with a value > 0.7. Average Variance Extracted (AVE) value > 0.5 and Composite Reliability value > 0.7. The two measurements of the inner model consist of r2 with a value of 0.539 for path I and 0.568 for path II. Then the f2 value of attitudes towards using of behavior intentions to use is 0.451, perceived ease of use of attitudes towards using are 0.380, perceived usefulness to attitudes towards using are 0.155, and perceived usefulness to behavior intentions to use are 0.112. The VIF value is smaller than (<0.5) so that there is no multicollinearity problem. The conclusion of this study states that all hypotheses are accepted.